Effects of asbestos and smoking on gas diffusion in people exposed to crocidolite - Alfonso, Helman; Fritschi, L.; De Klerk, N.; Olsen, N.; Sleith, J.; Musk, A. (Australasian Medical Publishing Company, 2005)
OBJECTIVE: To examine the effects of asbestos exposure and tobacco smoking on the level and rate of change of the diffusing capacity of the lung for carbon monoxide (DLCO). DESIGN AND PARTICIPANTS: A cohort study of 934 people (including both mine workers and town residents) exposed to crocidolite (blue asbestos) at the asbestos mines and in the town of Wittenoom, Western Australia, between 1943 and 1966. DLCO measurements were taken during a follow-up period from 1992 to 2002. MAIN OUTCOME MEASURES: Baseline levels of DLCO and change in levels over time. RESULTS: 2980 DLCO measurements were done on 934 people (of whom 818 were men and 724 were workers) who underwent a median of 2 (range, 1-17) measurements during the follow-up period. Radiographic asbestosis at baseline and asbestos exposure at a younger age were associated with lower DLCO values. The average rate of decline in DLCO was 0.33 (95% CI, 0.31-0.35) units per year, plus an additional decrement of 0.22 (95% CI, 0.12-0.32) units per year if the participant had radiographic asbestosis at the beginning of the follow-up period. Compared with never-smokers, current smokers and ex-smokers had lower DLCO at baseline, but smoking status did not affect the change in DLCO during the follow-up period. CONCLUSIONS: Our results confirm a continuous deleterious effect of crocidolite on DLCO, especially on people with asbestosis. Smoking was associated with lower DLCO levels, but was not a significant predictor of rate of change in DLCO. Smoking status did not affect the relationships between crocidolite exposure and the level or rate of change of DLCO in this population.